1993
DOI: 10.2307/1939318
|View full text |Cite
|
Sign up to set email alerts
|

Rapid N^2 Fixation in Pines, Alder, and Locust: Evidence From the Sandbox Ecosystems Study

Abstract: Not all nitrogen (N) inputs have been accounted for in forested ecosystems. We sought to account for N2 fixation and dry deposition using a lysimeter mass—balance approach. Large sand—filled, field lysimeters were used to construct 5—yr nitrogen budgets for two N2—fixing trees, two pines, and a nonvegetated control soil. This approach is a promising and straightforward technique for quantifying otherwise difficult—to—measure fluxes. Accurate assessment of changes in N storage combined with direct measurement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 46 publications
1
61
1
Order By: Relevance
“…This resulted in higher plant nitrogen residence time and, in turn, higher totals plant nitrogen in P. strobus. In addition, this nitrogen was derived from the soil nitrogen pool and not from nitrogen fixation as has been hypothesized previously (37).…”
Section: Resultsmentioning
confidence: 94%
“…This resulted in higher plant nitrogen residence time and, in turn, higher totals plant nitrogen in P. strobus. In addition, this nitrogen was derived from the soil nitrogen pool and not from nitrogen fixation as has been hypothesized previously (37).…”
Section: Resultsmentioning
confidence: 94%
“…An important trait of some endophytes is the ability to supply nitrogen to their host plant through biological nitrogen fixation. Nitrogen-fixing endophytes have been isolated from a variety of species, such as sugarcane [12], wild rice [13], corn [14,15], African sweet potato [16], kallar grass [17], coffee [18], cactus [19] and woody plants, including poplar, willow and coniferous trees [20][21][22][23]. It has been demonstrated that N fixed by diazotrophic bacteria can be utilized by plants [24].…”
Section: Introductionmentioning
confidence: 99%
“…After only four to five years, we found significant nitrogen gains that could not be accounted for by measured inputs (19). In the case of black alder and black locust, known symbiotic nitrogen fixers, we attributed those gains to symbiotic nitrogen fixation.…”
Section: The Sandbox Experimentsmentioning
confidence: 65%